Experiential Learning: The Case of Training MBA Students in an Asian School - Chiyachantana, Chiraphol N; Ding, David K; Hong, Jack J (International Journal of Educational Technology and Learning, 2022)
Consulting for a startup company is an effective way for Master of Business Administration (MBA) students to learn about management consulting, and the ways and means of a startup company. This paper discusses the experience of an MBA startup project within the context of a core corporate finance course. The project requires the active engagement of several groups of stakeholders—MBA students, the university’s entrepreneurship incubator, a selection of startup companies, and the project’s academic collaborators. In line with the literature, we find that entrepreneurship education through student-startup collaboration contributes to the students’ entrepreneurial learning, and that the offering of an experiential learning course provides students with the opportunities to work with the external business community that yield positive benefits for students, startups, and the university. Our findings add to the experiential learning literature in business education and show that practice-based learning offers an effective learning experience for students whereby all stakeholders are exposed to various communities of practice that facilitate multiple streams of learning. We provide insights on experiential learning from the implementation of a “new” learning pedagogy for MBA students at an Asian institute of higher learning.